Gender wage gap in hospitality management: The evidence in Europe - Lidia de Castro Romero; Víctor Martín; Rosa Santero Sánchez (Annals of Tourism Research Empirical Insights, 2025)
Hospitality employs many women, offering a chance to promote gender equality. However, wage disparities and unequal working conditions persist for women. This study examines the gender wage gap in managerial positions within hospitality across fourteen European countries, using data from the 2018 European Structure of Earnings Survey. We compute adjusted gender wage gaps and use decomposition methods to analyse wage disparities. Results show a significant wage gap in eight countries, from 5.1 % to 23.8 %, suggesting unobserved factors indicative of discrimination. Furthermore, we observe that in most countries, this gender wage gap is lower compared to other sectors of the economy. Additionally, much of the gap is due to female managers being concentrated in lower-paying establishments.
Keywords: 330; Decomposition methods; Gender discrimination; Gender wage gap; Hospitality; Management; Wage disparities